Environmental sustainability in veterinary clinics: best practices for the United States and Canada - Kern-Allely, Caroline; Scott, Danielle; Clow, Katie; Duncan, Colleen (Frontiers in Veterinary Science, 2025)
IntroductionVeterinary professionals in the United States and Canada are increasingly seeking ways to reduce the environmental impacts of clinical practice, reflecting a broader commitment within the profession to sustainability. While environmental sustainability frameworks are well established in human healthcare, equivalent resources for veterinary clinical practice in North America remain limited. This study aimed to develop evidence-based best practices for enhancing environmental sustainability in veterinary clinics in the United States and Canada.MethodsWe conducted a gray literature review of open-access resources in veterinary medicine and human healthcare to identify explicit sustainability actions. Extracted actions were synthesized and reviewed by a panel of seven subject matter experts through a two-round modified Delphi process. Experts evaluated each action for implementation effort and environmental impact and provided qualitative feedback.ResultsThe final set comprised 199 actions, organized into 14 thematic categories. Experts emphasized the importance of leadership engagement, team empowerment, and balancing high-impact, resource-intensive interventions with low-effort “quick wins” to build momentum. Priority areas included energy efficiency, waste reduction (particularly anesthetic gas management), sustainable procurement, and community engagement.DiscussionThe resulting framework provides a flexible, regionally relevant roadmap that clinics can adapt to their context, offering practical entry points for immediate action alongside strategies for long-term change. This resource can support veterinary teams, educators, and industry stakeholders in embedding sustainability into clinical practice, contributing to improved planetary and animal health.